The law of small things : creating a habit of integrity in a culture of mistrust - Brody, Stuart H. (Berrett-Koehler Publishers, 2019)
This book offers an IQ (Integrity Quotient) test designed to reveal the casual way we regard our promises and the misconceptions we have about acting truthfully. It discusses the changeability of integrity, the deceptions we deploy to appear to act with integrity without doing so, and the encouragement of breaches of integrity through "permitted promise-breaking," language that equates self-interest with duty, and the "illusion of inconsequence" that excuses small breaches